2012
DOI: 10.1515/1935-1682.3217
|View full text |Cite
|
Sign up to set email alerts
|

Green Jobs and Renewable Electricity Policies: Employment Impacts of Ontario's Feed-in Tariff

Abstract: Policy makers justify renewable energy promotion policies partly on the grounds that such policies have positive employment impacts. We apply a computable general equilibrium model to assess the labour market impacts of the feed-in tariff policy used by the Government of Ontario. We find that although the policy is successful at increasing the employment in the `green' sectors of the economy, the policy is also likely to increase the rate of unemployment in the province, and to reduce overall labour force pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 3 publications
1
22
0
1
Order By: Relevance
“…This fixed factor reflects the capacity restrictions of each generation technology [36][37][38][39] and is combined with other inputs consisting of intermediate composites and labor inputs to produce electricity. The substitution elasticities of σ within the CES production structure are calibrated consistently with exogenously-given supply elasticities of each generation technology [40,41]. Supply elasticity can represent how flexibly each technology can change its generation capacity in response to demand.…”
Section: Modeling the Electricity Sectormentioning
confidence: 99%
“…This fixed factor reflects the capacity restrictions of each generation technology [36][37][38][39] and is combined with other inputs consisting of intermediate composites and labor inputs to produce electricity. The substitution elasticities of σ within the CES production structure are calibrated consistently with exogenously-given supply elasticities of each generation technology [40,41]. Supply elasticity can represent how flexibly each technology can change its generation capacity in response to demand.…”
Section: Modeling the Electricity Sectormentioning
confidence: 99%
“…The economy as a whole typically reacts quite sensibly to energy price increases by lowering output and thus laying off workers. Recent CGE studies show the overall employment effects triggered by the deployment of RES-E to be typically negative (Böhringer et al 2012, Böhringer et al 2013). …”
Section: Providing New Employment Opportunities and Creating Green Jomentioning
confidence: 99%
“…Additionally, to the extent that increased wind impacts the cost of energy, or has other macroeconomic effects, this too may affect employment in the broader economy. Studies that have evaluated the economy-wide net effects of renewable energy have shown differing results (e.g., Böhringer et al 2013;Böhringer et al 2012;Bowen et al 2013;Breitschopf et al 2011;Chien and Hu 2008;Frondel et al 2010;Hillebrand et al 2006;Lehr et al 2012;Lehr et al 2008;Marques and Fuinhas 2012;Menegaki 2011;Rivers 2013;Yi 2013). In general, however, there is little reason to believe that net impacts are likely to be sizable in either the positive or negative direction (e.g., Rivers 2013).…”
Section: Workforce and Economic Developmentmentioning
confidence: 99%